Retreatment regimen of rituximab monotherapy given at the relapse of severe HCV-related cryoglobulinemic vasculitis: Long-term follow up data of a randomized controlled multicentre study. (September 2015) - Quartuccio, Luca; Zuliani, Francesca; Corazza, Laura; Scaini, Patrizia; Zani, Roberta; Lenzi, Marco; Tavoni, Antonio; Sebastiani, Marco; Baldovino, Simone; Urraro, Teresa; Saccardo, Francesco; Sbreglia, Costanza; et al.
Abstract: Objective: To evaluate the efficacy and safety in the long term of a retreatment regimen with Rituximab (RTX) alone administered at clinical relapse in cryoglobulinemic vasculitis (CV). Methods: Thirty patients with severe HCV-related CV, previously enrolled in the multicentre Italian trial on RTX in the treatment of CV, were retrospectively evaluated after the end of the trial. All of them were managed with RTX alone at clinical relapse, if any. Disease activity at the last available follow up was defined as complete remission (absence of active disease), partial remission (response > 50% of at least one manifestation among glomerulonephritis, peripheral neuropathy or skin ulcers) or active disease. Results: The mean follow up after the first RTX cycle was 72.6 (20.4) months. After the end of the trial, 21/30 (70%) patients showed an active follow up [81.7 (10.9) months)], 3/30 (10%) lost follow up and 6/30 (20%) died. 12/21 (57.1%) patients were in complete disease remission, 5/21 (23.8%) showed a partial response and 4/21 (19%) had an active disease. 17/30 (56.7%) patients needed retreatment for relapse with a mean time to retreatment of 22.3 (12.1) months. Treatment survival of this regimen was 7.6 (0.3) years. Recurrent non-severe infections occurred in 3/30, with chronic hypogammaglobulinemia in 2/3 patients. Conclusions: A long-term regimen of retreatment with RTX alone given at clinical relapse seems to be effective and safe in CV, with a low rate of infections and severe hypogammaglobulinemia. Highlights: Rituximab retreatment at clinical relapse appears useful in the long term for severe cryoglobulinemic vasculitis. Rituximab retreatment at clinical relapse is associated with a low incidence of severe hypogammaglobulinemia. Rituximab retreatment at clinical relapse saves on the use of glucocorticoids in severe cases of cryoglobulinemic vasculitis.